Separator for electrochemical device, method for producing same and electrochemical device including same
Patent Information
- Application Number
- JP2024549156
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-10-05
- Filing Date
- 2023-09-05
- Publication Date
- 2025-03-26
AI Technical Summary
【0025】 本発明の一実施態様による電気化学素子用分離膜は、無機粒子と高分子バインダーとの間の凝集力を向上させ、高分子基材とコーティング層との間の接着力を向上させることができる。
Smart Images

Figure 2025508442000001_ABST
Abstract
Description
[Technical field]
[0001] This invention claims the benefit of the filing date of Korean Patent Application No. 10-2022-0126886, filed with the Korean Intellectual Property Office on October 5, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a separator for an electrochemical device, a manufacturing method thereof, and an electrochemical device including the same, and more particularly, to a separator for an electrochemical device, which can form a coating layer using a polymer binder mixture including a plurality of polymer binders having different glass transition temperatures, thereby improving cohesive force between the polymer binders and preventing the coating layer from being detached from a polymer substrate, a manufacturing method thereof, and an electrochemical device including the same. [Background technology]
[0003] The separator, which is a component of an electrochemical device, includes a polymer substrate having a porous structure disposed between the positive and negative electrodes, and serves to isolate the positive and negative electrodes, prevent electrical shorting between the two electrodes, and allow electrolytes and ions to pass through. The separator itself does not participate in the electrochemical reaction, but its physical properties, such as wettability with respect to the electrolyte, degree of porosity, thermal shrinkage rate, etc., affect the performance and safety of the electrochemical device.
[0004] Therefore, in order to enhance the physical properties of the separation membrane, various methods have been tried to add a coating layer to the porous polymer substrate and to change the physical properties of the coating layer by adding various substances to the coating layer. For example, an inorganic substance may be added to the coating layer to improve the mechanical strength of the separation membrane, or an inorganic substance or a hydrate may be added to the coating layer to improve the flame retardancy and heat resistance of the polymer substrate.
[0005] The separator may be attached to the electrode by a lamination process, and a polymer binder may be added to a composition for forming a coating layer of the separator to ensure adhesion between the electrode and the separator.
[0006] Meanwhile, when exposed to high temperatures, the porous polymer substrate may shrink. If the separator shrinks in a lithium-ion battery, the positive and negative electrodes may come into contact with each other, causing an internal short circuit, and thermal runaway may occur due to a decomposition reaction between the electrolyte and the active material.
[0007] Furthermore, in the past, there was active research into a technology in which the surface of a polymer substrate is coated with an inorganic material to suppress thermal shrinkage by using the adhesive strength between the polymer substrate and the inorganic coating layer. However, in reality, there was a problem that the electrolyte in the battery weakens the adhesive strength between the polymer and the inorganic material, and the adhesive strength at high temperatures is reduced, making it impossible to ensure high-temperature thermal stability, resulting in shrinkage.
[0008] Therefore, currently, research is needed into technology that can minimize the decrease in the adhesive strength of the coating layer contained in the separator. Summary of the Invention [Problem to be solved by the invention]
[0009] The technical problem to be solved by the present invention is to provide a separator for an electrochemical device, which can improve the cohesion between inorganic particles and a polymer binder and prevent a coating layer from being detached due to impact during the process of cutting and handling the separator and during the process of assembling a battery, a manufacturing method thereof, and an electrochemical device including the same.
[0010] However, the problems to be solved by the present invention are not limited to those mentioned above, and other problems not mentioned will be clearly understood by those skilled in the art from the following description. [Means for solving the problem]
[0011] One embodiment of the present invention provides a separator for an electrochemical device, comprising: a polymer substrate having a plurality of pores; and a coating layer provided on at least one surface of the polymer substrate, the coating layer having a plurality of pores and comprising inorganic particles and a polymer binder mixture, the polymer binder mixture comprising three or more polymer binders having different glass transition temperatures.
[0012] According to one embodiment of the present invention, the polymeric binder mixture includes a first polymeric binder, a second polymeric binder and a third polymeric binder, and the first polymeric binder, the second polymeric binder and the third polymeric binder may satisfy the following formula 1:
[0013] [Formula 1] The glass transition temperature of the first polymer binder < the glass transition temperature of the second polymer binder < the glass transition temperature of the third polymer binder.
[0014] According to one embodiment of the present invention, the glass transition temperature of the first polymer binder may be in the range of -40°C to -20°C.
[0015] According to an embodiment of the present invention, the second polymer binder may have a glass transition temperature of 0°C or more and 20°C or less.
[0016] According to an embodiment of the present invention, the glass transition temperature of the third polymer binder may be 30°C or more and 60°C or less.
[0017] According to one embodiment of the present invention, the first polymer binder may have a glass transition temperature of -40°C or more and -20°C or less, the second polymer binder may have a glass transition temperature of 0°C or more and 20°C or less, and the third polymer binder may have a glass transition temperature of 30°C or more and 60°C or less.
[0018] According to one embodiment of the present invention, the content of the first polymer binder may be 5 parts by weight or more and 15 parts by weight or less, based on 100 parts by weight of the polymer binder mixture, the content of the second polymer binder may be 30 parts by weight or more and 50 parts by weight or less, based on 100 parts by weight of the polymer binder mixture, and the content of the third polymer binder may be 40 parts by weight or more and 60 parts by weight or less, based on 100 parts by weight of the polymer binder mixture.
[0019] According to one embodiment of the present invention, the content of the first polymer binder in a portion of the thickness of the coating layer adjacent to the polymer substrate may be greater than the content of the first polymer binder in another portion not adjacent to the polymer substrate.
[0020] According to one embodiment of the present invention, the content of the third polymer binder in a portion of the thickness of the coating layer that is not adjacent to the polymer substrate may be greater than the content of the third polymer binder in a portion of the thickness of the coating layer that is adjacent to the polymer substrate.
[0021] According to an embodiment of the present invention, the second polymer binder may be contained in the coating layer at a uniform content.
[0022] One embodiment of the present invention provides a method for producing a separator for an electrochemical device, the method including: coating at least one surface of the polymer substrate with a composition for forming a coating layer, the composition including the inorganic particles and a polymer binder mixture including three or more polymer binders having different glass transition temperatures; and drying the coated composition for forming a coating layer to form the coating layer.
[0023] According to one embodiment of the present invention, the temperature in the drying step may be 30°C or more and 70°C or less.
[0024] One embodiment of the present invention provides an electrochemical device, comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, the separator being a separator for an electrochemical device. Effect of the Invention
[0025] A separator for an electrochemical device according to an embodiment of the present invention can improve the cohesive force between inorganic particles and a polymer binder, and can improve the adhesive force between a polymer substrate and a coating layer.
[0026] In a method for manufacturing a separator for an electrochemical device according to an embodiment of the present invention, the cohesive strength between the inorganic particles and the polymer binder can be improved by controlling the temperature during the drying process, and the adhesive strength between the polymer substrate and the coating layer and the adhesive strength between the electrode and the coating layer can be improved by controlling the contents of the first polymer binder and the third polymer binder according to the position of the coating layer.
[0027] In an electrochemical device according to an embodiment of the present invention, the coating layer can be prevented from being detached due to impact during cutting and handling of the separator and during assembly of the battery.
[0028] The effects of the present invention are not limited to the effects described above, and effects not mentioned herein will be clearly understood by those skilled in the art from the present specification and the accompanying drawings. [Brief description of the drawings]
[0029] [Figure 1] 1 is a schematic diagram of a separator for an electrochemical device according to an embodiment of the present invention.
[0030] [Diagram 2] 1 is a flow diagram of a method for producing a separator for an electrochemical device according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] The following examples of the present invention are provided to more clearly explain the present invention to those skilled in the art, and the scope of the present invention is not limited to the following examples, which may be modified in various other forms.
[0032] The terms used in this specification are used to describe specific embodiments and are not intended to limit the present invention. As used in this specification, singular terms can include plural forms unless otherwise clearly indicated in the context.
[0033] The terms "comprise" and / or "comprising" as used herein specify the presence of stated features, steps, numbers, operations, members, elements and / or groups thereof, but do not exclude the presence or addition of one or more other features, steps, numbers, operations, members, elements and / or groups thereof.
[0034] The term "connected" as used in this specification does not only mean that certain components are directly connected to each other, but also includes the concept of indirectly connecting components through the intermediation of other components.
[0035] In this specification, when a member is described as being disposed "on" another member, this includes not only the case where the member is in contact with the other member, but also the case where there is another member between the two members.
[0036] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0037] As used in this specification, terms of degree such as "about," "substantially," and the like are used to mean a range of values or degrees or close thereto, taking into consideration inherent manufacturing and material tolerances, and are used to prevent infringers from unfairly exploiting the disclosure content in which precise and absolute values provided to aid in the understanding of this application are mentioned.
[0038] As used herein, the characteristic of "having pores" means that an object contains a plurality of pores, and that the pores have an interconnected structure that allows gas and / or liquid fluids to pass from one side of the object to the other side of the object.
[0039] In this specification, the separator has a porous characteristic including a large number of pores and serves as a porous ion-conducting barrier that allows ions to pass while blocking electrical contact between the negative electrode and the positive electrode in the electrochemical device.
[0040] The present invention will be described in further detail below.
[0041] One embodiment of the present invention provides a separator for an electrochemical device, comprising: a polymer substrate having a plurality of pores; and a coating layer provided on at least one surface of the polymer substrate, the coating layer having a plurality of pores and comprising inorganic particles and a polymer binder mixture, the polymer binder mixture comprising three or more polymer binders having different glass transition temperatures.
[0042] A separator for an electrochemical device according to an embodiment of the present invention can improve the cohesive force between inorganic particles and a polymer binder, and can improve the adhesive force between a polymer substrate and a coating layer.
[0043] 1 is a schematic diagram of a separator for an electrochemical device 100 according to an embodiment of the present invention. The separator for an electrochemical device 100 according to an embodiment of the present invention will be described in detail with reference to FIG.
[0044] According to an embodiment of the present invention, the separator includes a polymer substrate 110 having a plurality of pores. In this specification, the polymer substrate having a plurality of pores may mean a porous polymer substrate or a porous membrane having a fine diameter of the pores. As described above, the separator for an electrochemical device includes the polymer substrate 110 having a plurality of pores, so that the separator can electrically insulate the anode and cathode to prevent short circuiting while allowing lithium ions to pass through, and when high-temperature runaway occurs during use of the battery, the polymer substrate melts to shut down the pores, thereby preventing thermal runaway of the battery. Furthermore, the polymer substrate serves as an ion-conducting barrier that allows ions to pass through while blocking electrical contact between the anode and cathode. A plurality of pores are formed inside the separator, and the pores are preferably connected to each other to allow gas or liquid to pass from one side of the separator to the other side.
[0045] According to one embodiment of the present invention, the polymer substrate 110 may be one having high resistance to the electrolyte, which is an organic solvent, and may be used without any particular limitation as long as it can be used as a material for the separator of a secondary battery. Specifically, the polymer substrate 110 may include resins such as polyolefins including polyethylene, polypropylene, and polybutene, polyvinyl chloride, polyethylene terephthalate, polycycloolefin, polyethersulfone, polyamide, polyimide, polyimideamide, polyaramid, polycycloolefin, nylon, polytetrafluoroethylene, and mixtures or copolymers thereof. Preferably, a polyolefin resin may be used, and more preferably, a polyethylene resin. Among these, polyolefin resins have excellent applicability of the mixture for forming the coating layer, and can reduce the thickness of the separator for the secondary battery, increase the ratio of the electrode active material layer in the battery, and increase the volumetric capacity.
[0046] According to an embodiment of the present invention, the thickness of the polymer substrate 110 may be 1 μm to 100 μm. Specifically, the thickness of the polymer substrate may be 10 μm to 95 μm, 15 μm to 90 μm, 20 μm to 85 μm, 25 μm to 80 μm, 30 μm to 75 μm, 35 μm to 70 μm, 40 μm to 65 μm, 45 μm to 60 μm, 50 μm to 65 μm, or 55 μm to 60 μm. Preferably, the thickness of the polymer substrate may be 1 μm to 30 μm. By adjusting the thickness of the polymer substrate within the above range, the volume of the electrochemical device can be minimized and the negative electrode and the positive electrode can be electrically insulated.
[0047] According to one embodiment of the present invention, the size of the pores contained in the polymer substrate may be 1 nm to 100 nm. Specifically, the size of the pores contained in the polymer substrate may be 5 nm to 95 nm, 10 nm to 90 nm, 15 nm to 85 nm, 20 nm to 80 nm, 25 nm to 75 nm, 30 nm to 70 nm, 35 nm to 65 nm, 40 nm to 60 nm, or 45 nm to 55 nm. Preferably, the size of the pores contained in the polymer substrate may be 20 nm to 60 nm. By adjusting the size of the pores contained in the polymer substrate within the above range, the permeability of lithium ions can be adjusted.
[0048] In one embodiment of the present invention, the pore size of the polymer-based material 110 and / or the coating layer 130 can be measured by a BET 6-point method using a scanning electron microscope (SEM) image, a mercury porosimeter, a capillary flow porometer, or a porosimetry analyzer (Belsorp-II mini, Bell Japan Inc.), a nitrogen gas adsorption flow method, etc. In this case, it may be advantageous to use a capillary flow porosimeter.
[0049] According to an embodiment of the present invention, the polymer substrate may be in the form of a porous sheet having a plurality of pores, the pores including open pores having a structure in which the pores are interconnected to each other, allowing gas or liquid to pass from one side of the polymer substrate to the other side.
[0050] According to one embodiment of the present invention, the polymer-based material preferably has an air permeability of 2000 sec / 100 ml or less and a porosity of 30 vol % to 60 vol % in terms of battery output and cycle characteristics.
[0051] In the present specification, the air permeability (sec / 100 ml) means the time (seconds) required for 100 ml of air to pass through a sample such as a polymeric substrate or a separation membrane having a size of 1 square inch under a certain air pressure. In the present specification, the air permeability can be measured according to the standard regulations in the technical field. Specifically, the air permeability can be measured using a Gurley Densometer known in the art according to ASTM D726-58 or ASTM D726-94, and for example, the air permeability can be measured using air at a pressure of 0.304 (kPa) or 1.215 kN / m 2 of water pressure in one square inch (or 6.54 cm 2 In yet another embodiment, the air permeability is measured at room temperature according to the Gurley method of the Japanese Industrial Standard (JIS-P8117) at 4.8 inches H. 2 It can be shown by measuring the time (seconds) it takes for 100 ml of air to pass through a sample of 1 square inch under a constant pressure of O. In one embodiment of the present invention, the air permeability can be measured, for example, using an Asahi Seico EG01-55-1MR device in accordance with the standard regulations.
[0052] In the present specification, the porosity means the ratio of the volume occupied by pores to the total volume, and is expressed in units of vol%. The porosity can be used interchangeably with terms such as porosity and porosity. In the present invention, the measurement of the porosity is not particularly limited, and a method known in the art can be applied. For example, the porosity can be measured by a BET (Brunauer-Emmett-Teller) measurement method using nitrogen gas, a water intrusion prosimeter method, a capillary flow porometer, or a mercury intrusion method (Hg porosimeter). Alternatively, in one embodiment of the present invention, the true density of the polymer substrate can be calculated from the density (apparent density) of the obtained polymer substrate, the composition ratio of the materials contained in the polymer substrate, and the density of each component, and the porosity of the polymer substrate can be calculated from the difference between the apparent density and the true density (net density). Specifically, the porosity can be calculated according to the following [Equation 2].
[0053] [Formula 2]
[0054] Porosity (vol%) = {1-(apparent density / true density)} x 100
[0055] On the other hand, in the above formula, the apparent density can be calculated from the following [Formula 3].
[0056] [Formula 3]
[0057] Apparent density (g / cm 3 ) = {Weight of polymer substrate [g] / (Thickness of polymer substrate [cm] × Area of polymer substrate [cm 2 ])}
[0058] According to one embodiment of the present invention, the coating layer 130 is provided on at least one surface of the polymer substrate 110, has a plurality of pores, and includes a mixture of inorganic particles and a polymer binder. As described above, by including the coating layer 130, which is provided on at least one surface of the polymer substrate 110, has a plurality of pores, and includes a mixture of inorganic particles and a polymer binder, the polymer substrate 110 can be prevented from shrinking at high temperatures, and the negative electrode and the positive electrode in the battery can be prevented from coming into contact with each other to cause an internal short circuit.
[0059] According to an embodiment of the present invention, the thickness of the coating layer 130 may be 0.1 μm to 20 μm. Specifically, the thickness of the coating layer may be 1 μm to 19 μm, 2 μm to 18 μm, 3 μm to 17 μm, 4 μm to 16 μm, 5 μm to 15 μm, 6 μm to 14 μm, 7 μm to 12 μm, 8 μm to 11 μm, or 9 μm to 10 μm. By adjusting the thickness of the coating layer within the above range, the thickness of the separator for an electrochemical device can be adjusted, weight reduction can be achieved, and shrinkage of the polymer base material at high temperatures can be prevented.
[0060] In one embodiment of the present invention, the thickness of the polymer base material and / or the coating layer can be measured using a contact thickness gauge, such as Mitutoyo's VL-50S-B.
[0061] According to one embodiment of the present invention, the coating layer 130 is provided on at least one surface of the polymer substrate 110. Specifically, the coating layer 130 is provided on one surface of the polymer substrate 110 or on both surfaces of the polymer substrate 110. As described above, by providing the coating layer 130 on at least one surface of the polymer substrate 110, it is possible to minimize shrinkage of the polymer substrate 110 at high temperatures.
[0062] According to one embodiment of the present invention, a coating layer may be formed using a composition for forming a coating layer including the inorganic particles and the polymer binder mixture. As described above, by using a composition for forming a coating layer including the inorganic particles and the polymer binder mixture, the convenience of the work for forming a coating layer can be improved, and the viscosity of the composition for forming a coating layer can be easily adjusted.
[0063] According to one embodiment of the present invention, the composition for forming a coating layer may further include a solvent. As described above, the composition for forming a coating layer may further include a solvent, which may improve the convenience of the operation for forming a coating layer, and may uniformly disperse the inorganic particles and the polymer binder mixture in the composition for forming a coating layer. In the present specification, the solvent may refer to a dispersion medium, and the emulsion in which the inorganic particles and the polymer binder mixture are dispersed by the solvent may refer to the composition for forming a coating layer.
[0064] According to one embodiment of the present invention, the solvent may be one selected from the group consisting of water, acetone, ethanol, isopropyl alcohol (IPA), dimethylacetamide (DMAc), dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), acetonitrile, and combinations thereof. Specifically, the solvent is preferably water. By selecting the solvent from the above, it is possible to adjust the viscosity of the composition for forming a coating layer and improve the dispersibility of inorganic particles and polymer binder in the solvent.
[0065] According to one embodiment of the present invention, the composition for forming a coating layer may further include an additive. As described above, by further including an additive in the composition for forming an inorganic coating layer, the binding strength of the inorganic particles can be improved, and the dispersibility of the composition for forming an inorganic coating layer can be improved.
[0066] According to one embodiment of the present invention, the additives may include dispersants, surfactants, defoamers, flame retardants, adhesion promoters, etc. By selecting the additives from the above, it is possible to improve the dispersibility and phase stability of the composition for forming an inorganic coating layer, remove bubbles, add flame retardancy, improve adhesion, and improve the wettability between the polymer substrate and the composition for forming a coating layer.
[0067] According to one embodiment of the present invention, the dispersant may be any one or more selected from polyacrylic acid, oil-soluble polyamine, oil-soluble amine compound, fatty acid, fatty alcohol, sorbitan fatty acid ester, tannic acid, and pyrogallic acid. Preferably, the dispersant may be polyacrylic acid (PAA). By selecting the dispersant from the above, the dispersibility and phase stability of the composition for inorganic coating layer can be improved.
[0068] According to one embodiment of the present invention, the content of the dispersant may be 0 to 5 parts by weight based on 100 parts by weight of the composition for forming a coating layer. Specifically, the content of the dispersant may be more than 0 to 5 parts by weight, 1 to 4 parts by weight, or 2 to 3 parts by weight based on 100 parts by weight of the composition for forming a coating layer. By adjusting the content of the dispersant within the above range, the dispersibility and phase stability of the composition for forming a coating layer can be improved.
[0069] According to an embodiment of the present invention, the coating layer 130 includes a plurality of pores. Specifically, the coating layer 130 includes a plurality of micropores. The plurality of pores may be micropores due to the interstitial volume formed between the inorganic particles, which is densely filled with the polymer binder and inorganic particles contained in the polymer binder mixture. These micropores are connected to each other, and show a porous structure through which gas or liquid can pass from one side to the other side. As described above, the coating layer 130 includes a plurality of pores, so that the electrolyte in the battery described later can pass through the separator.
[0070] According to an embodiment of the present invention, the coating layer 130 includes a coating layer including inorganic particles and a polymer binder mixture. Specifically, the coating layer 130 may be formed by coating a composition for forming a coating layer including inorganic particles and a polymer binder mixture on the polymer substrate, and evaporating a solvent included in the composition for forming a coating layer, so that the polymer binder included in the inorganic particles and the polymer binder mixture is densely packed to form a coating layer. As described above, the coating layer 130 includes a coating layer including inorganic particles and a polymer binder mixture, which allows the electrolyte to permeate the separator and prevents the separator from thermally shrinking at high temperatures.
[0071] According to one embodiment of the present invention, the content of the inorganic particles may be 80 parts by weight or more and 95 parts by weight or less, based on 100 parts by weight of the composition for the coating layer. Specifically, the content of the inorganic particles may be 81 parts by weight or more and 94 parts by weight or less, 82 parts by weight or more and 93 parts by weight or less, 83 parts by weight or more and 92 parts by weight or less, 84 parts by weight or more and 91 parts by weight or less, 85 parts by weight or more and 90 parts by weight or less, 86 parts by weight or more and 89 parts by weight or less, or 87 parts by weight or more and 88 parts by weight or less, based on 100 parts by weight of the composition for the inorganic coating layer. By controlling the content of the inorganic particles within the above range, the insulating property and heat resistance of the separator can be improved, and the phenomenon of the separator shrinking at high temperatures can be prevented.
[0072] According to one embodiment of the present invention, the inorganic particles are not particularly limited as long as they are electrochemically stable. That is, the inorganic particles that can be used in the present invention are those that can be used in the operating voltage range (e.g., Li / Li + There are no particular limitations on the inorganic particles, so long as they do not undergo oxidation and / or reduction reactions at a voltage of 0 to 5 V (based on the reference). In particular, when inorganic particles having a high dielectric constant are used as the inorganic particles, they can contribute to increasing the degree of dissociation of electrolyte salts, such as lithium salts, in the liquid electrolyte, thereby improving the ionic conductivity of the electrolyte. For the reasons described above, it is preferable that the inorganic particles include high-dielectric-constant inorganic particles having a dielectric constant of 5 or more, preferably 10 or more. Non-limiting examples of inorganic particles having a dielectric constant of 5 or more include BaTiO 3 , Pb(Zr,Ti)O 3 (PZT), Pb 1-x La x Zr 1-y Ti y O 3 (PLZT, 0 <x<1、0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3 )O 3 -PbTiO 3 (PMN-PT), hafnia (HfO 2 ), SrTiO 3 , SnO 2 , CEO 2 , MgO, NiO, CaO, ZnO, ZrO 2 , SiO2 , Y 2 O 3 , Al 2 O 3 , Al(OH) 3 , SiC, AlOOH and TiO 2 Or a mixture of these.
[0073] In addition, inorganic particles having lithium ion transfer ability, that is, inorganic particles containing lithium element but having the function of transferring lithium ions without storing lithium, can be used as the inorganic particles. Non-limiting examples of inorganic particles having lithium ion transfer ability include lithium phosphate (Li 3 PO 4 ), lithium titanium phosphate (Li x Ti y (PO 4 ) 3 , 0 <x<2、0<y<3)、リチウムアルミニウムチタニウムホスフェート(Li x Al y Ti z (PO 4 ) 3 , 0 <x<2、0<y<1、0<z<3)、14Li 2 O-9Al 2 O 3 -38TiO 2 -39P 2 O 5 Such as (LiAlTiP) x O y Glass (0 <x<4、0<y<13)、リチウムランタンチタネート(Li x La y TiO 3 , 0 <x<2、0<y<3)、Li 3.25 Ge 0.25 P 0.75 S 4 Lithium germanium thiophosphate (Li x Ge y P z S w , 0 <x<4、0<y<1、0<z<1、0<w<5)、Li 3 Lithium nitride (LiN) x Ny 、 0 < x < 4, 0 < y < 2), Li 3 PO 4 -Li 2 S - SiS 2 such as SiS 2 system glass (Li x Si y S z 、 0 < x < 3, 0 < y < 2, 0 < z < 4), LiI - Li 2 S - P 2 S 5 such as P 2 S 5 system glass (Li x P y S z 、 0 < x < 3, 0 < y < 3, 0 < z < 7) or mixtures thereof, etc.
[0074] According to one embodiment of the present invention, the average particle size (D50) of the inorganic particles may be 50 nm or more and 5,000 nm or less. Specifically, the average particle size (D50) of the inorganic particles may be 100 nm or more and 4,500 nm or less, 200 nm or more and 4,000 nm or less, 300 nm or more and 3,000 nm or less, 400 nm or more and 2,000 nm or less, or 500 nm or more and 1,000 nm or less. When the average particle size of the inorganic particles is less than 50 nm, as the specific surface area increases, an additional polymer binder for bonding between the inorganic particles becomes necessary, which is disadvantageous in terms of electrical resistance. Also, the greater the amount of the existing polymer binder, the lower the peel strength and polymer binder peeling can be. When the average particle size of the inorganic particles exceeds 5,000 nm, the uniformity of the coating layer surface becomes low. Also, if the size of the particles protruding after coating is large, the separation film and the electrode may be damaged during lamination, and a short circuit may occur.
[0075] According to one embodiment of the present invention, the aspect ratio of the inorganic particles may be 1 or more and 2 or less. Specifically, the aspect ratio of the inorganic particles may be 1.2 or more and 1.8 or less, 1.3 or more and 1.7 or less, or 1.4 or more and 1.6 or less. By controlling the aspect ratio of the inorganic particles within the above range, the polymer binder can easily move through the pores between the inorganic particles, and in particular, the smaller the aspect ratio as a monodisperse particle and the smaller the BET specific surface area, the better the movement of the polymer binder in the coating layer.
[0076] According to one embodiment of the present invention, the BET specific surface area of the inorganic particles is 5 m 2 / g or more 25m 2 Specifically, the BET specific surface area of the inorganic particles may be 6 m 2 / g or more 24m 2 / g or less, 7m 2 / g or more 23m 2 / g or less, 8m 2 / g or more 22m 2 / g or less, 9m 2 / g or more 21m 2 / g or less, 10m 2 / g or more 20m 2 / g or less, 11m 2 / g or more 19m 2 / g or less, 12m 2 / g or more 18m 2 / g or less, 13m 2 / g or more 17m 2 / g or less or 14m 2 / g or more 26m 2 By adjusting the BET specific surface area of the inorganic particles within the above range, the polymer binder can easily move through the pores between the inorganic particles, and in particular, the smaller the aspect ratio and the smaller the BET specific surface area in the case of monodispersion, the better the movement of the polymer binder in the coating layer.
[0077] In this specification, the BET surface area can be measured using the BET (Brunauer, Emmett and Teller) model adsorption equation, and is the measured N surface area when the adsorption isotherm is measured up to 1 bar (1 atmosphere) at the boiling point temperature of nitrogen of -196 °C. 2 The amount of adsorption can be measured and calculated from the adsorption isotherm.
[0078] According to one embodiment of the present invention, the polymer binder mixture includes three or more polymer binders having different glass transition temperatures. As described above, the polymer binder mixture includes three or more polymer binders having different glass transition temperatures, which can improve the adhesive strength between the polymer substrate and the coating layer, increase the contact area between the other polymer binders and the inorganic particles to improve the cohesive strength, prevent the dry adhesive strength from decreasing, and prevent the adhesive strength between the electrode and the separator from decreasing due to the polymer binder sinking under the inorganic particles.
[0079] According to one embodiment of the present invention, each of the three or more polymer binders having different glass transition temperatures may be in the form of particles. As described above, by utilizing the fact that each of the three or more polymer binders having different glass transition temperatures is in the form of particles, in the porous coating layer, the inorganic particles and the polymer binder are filled and in contact with each other, and the inorganic particles are bound to each other by the binder polymer, so that an interstitial volume can be formed between the inorganic particles, and the interstitial volume between the inorganic particles can become a void space to form a pore. That is, the polymer binder bonds the inorganic particles to each other so that the inorganic particles can be maintained in a bound state, that is, the polymer binder can connect and fix the inorganic particles. In addition, the pores of the coating layer are pores formed when the interstitial volume between the inorganic particles becomes a void space, and this may be a space limited by the inorganic particles that are substantially in contact with each other in a packed structure (closely packed or densely packed) by the inorganic particles.
[0080] According to one embodiment of the present invention, the polymer binder mixture may include a first polymer binder, a second polymer binder, and a third polymer binder, and the first polymer binder, the second polymer binder, and the third polymer binder may satisfy the following mathematical formula 1. As described above, when the polymer binder mixture includes a first polymer binder, a second polymer binder, and a third polymer binder, and the first polymer binder, the second polymer binder, and the third polymer binder satisfy the following mathematical formula 1, the adhesive strength between the polymer substrate and the coating layer can be improved, the contact area between the other polymer binder and the inorganic particles can be increased to improve the cohesive strength, and the dry adhesive strength can be prevented from decreasing, and the adhesive strength between the electrode and the separator can be prevented from decreasing due to the polymer binder sinking under the inorganic particles.
[0081] [Formula 1]
[0082] Glass transition temperature of the first polymer binder < Glass transition temperature of the second polymer binder < Glass transition temperature of the third polymer binder
[0083] According to one embodiment of the present invention, the glass transition temperature of the first polymer binder may be -40°C to -20°C. The glass transition temperature of the first polymer binder may be -39°C to -21°C, -38°C to -22°C, -37°C to -23°C, -36°C to -24°C, -35°C to -25°C, -34°C to -26°C, -33°C to -27°C, -32°C to -28°C, or -31°C to -29°C. By controlling the glass transition temperature of the first polymer binder within the above range, the shape of the polymer binder is maintained during the drying process, and the adhesive strength between the polymer substrate and the coating layer is prevented from decreasing, and the adhesive strength of the polymer binder itself is prevented from decreasing.
[0084] According to an embodiment of the present invention, the glass transition temperature of the second polymer binder may be 0° C. to 20° C. In particular, the glass transition temperature of the second polymer binder may be 1° C. to 19° C., 2° C. to 18° C., 3° C. to 17° C., 4° C. to 16° C., 5° C. to 15° C., 6° C. to 14° C., 7° C. to 13° C., 8° C. to 12° C., or 9° C. to 11° C. By controlling the glass transition temperature of the second polymer binder within the above range, when sufficient cohesive strength is not secured in the course of drying a conventional separator and the temperature is increased to secure sufficient cohesive strength, the shape of the third polymer binder is distorted, and the dry adhesive strength is reduced, thereby preventing the cohesive strength from being reduced.
[0085] According to an embodiment of the present invention, the glass transition temperature of the third polymer binder may be 30° C. to 60° C. In particular, the glass transition temperature of the third polymer binder may be 31° C. to 59° C., 32° C. to 58° C., 33° C. to 57° C., 34° C. to 56° C., 35° C. to 55° C., 36° C. to 54° C., 37° C. to 53° C., 38° C. to 52° C., 39° C. to 51° C., 40° C. to 50° C., 41° C. to 49° C., 42° C. to 48° C., 43° C. to 47° C., or 44° C. to 46° C. By controlling the glass transition temperature of the third polymer binder within the above range, it is possible to prevent the polymer binder from sinking below the inorganic particles, thereby preventing a decrease in adhesive strength between the electrode and the separator.
[0086] According to one embodiment of the present invention, the first polymer binder may have a glass transition temperature of -40° C. to -20° C., the second polymer binder may have a glass transition temperature of 0° C. to 20° C., and the third polymer binder may have a glass transition temperature of 30° C. to 60° C. It has been confirmed that by controlling the glass transition temperatures of the first polymer binder, the second polymer binder, and the third polymer binder all within the above ranges, the adhesive strength between the electrode and the separator is maintained and the cohesive strength and peel strength are improved.
[0087] According to an embodiment of the present invention, the weight average molecular weight of each of the first polymer binder, the second polymer binder, and the third polymer binder may be 1,000 to 10,000,000. Specifically, the weight average molecular weight of each of the first polymer binder, the second polymer binder, and the third polymer binder may be 1,000 to 10,000,000, 10,000 to 9,000,000, 100,000 to 8,000,000, 200,000 to 7,000,000, 300,000 to 6,000,000, 500,000 to 5,000,000, 1,000,000 to 4,000,000, or 2,000,000 to 3,000,000. By controlling the weight average molecular weight of each of the first polymer binder, the second polymer binder, and the third polymer binder within the above-mentioned range, the mechanical properties of the coating layer can be realized and the adhesive strength with the polymer substrate can be improved.
[0088] In this specification, the weight average molecular weight (Mw) can be measured by gel permeation chromatography (GPC, PL GPC220, Agilent Technologies), and the measurement conditions can be set as follows.
[0089] - Column: PL Olexis (Polymer Laboratories)
[0090] -Solvent: TCB (Trichlorobenzene)
[0091] -Flow rate: 1.0ml / min
[0092] -Sample concentration: 1.0mg / ml
[0093] -Injection volume: 200μL
[0094] -Column temperature: 160°C
[0095] -Detector:Agilent High TemperatureRI detector
[0096] -Standard:Polystyrene (corrected by cubic function)
[0097] According to one embodiment of the present invention, the content of the first polymer binder may be 5 parts by weight or more and 15 parts by weight or less, based on 100 parts by weight of the polymer binder mixture. Specifically, the content of the first polymer binder may be 6 parts by weight or more and 14 parts by weight or less, 7 parts by weight or more and 13 parts by weight or less, 8 parts by weight or more and 12 parts by weight or less, or 9 parts by weight or more and 11 parts by weight or less, based on 100 parts by weight of the polymer binder mixture. By adjusting the content of the first polymer binder within the above range, the adhesive strength between the polymer substrate and the coating layer can be improved.
[0098] According to one embodiment of the present invention, the content of the second polymer binder may be 20 parts by weight to 40 parts by weight based on 100 parts by weight of the polymer binder mixture. Specifically, the content of the second polymer binder may be 11 parts by weight to 39 parts by weight, 22 parts by weight to 38 parts by weight, 23 parts by weight to 37 parts by weight, 24 parts by weight to 36 parts by weight, 25 parts by weight to 35 parts by weight, 26 parts by weight to 34 parts by weight, 27 parts by weight to 33 parts by weight, 28 parts by weight to 32 parts by weight, or 29 parts by weight to 31 parts by weight based on 100 parts by weight of the polymer binder mixture. By controlling the content of the second polymer binder within the above range, the contact area between the other polymer binder and the inorganic particles is increased to improve the cohesive force and prevent the dry adhesive force from decreasing.
[0099] According to an embodiment of the present invention, the content of the third polymer binder may be 50 parts by weight to 70 parts by weight based on 100 parts by weight of the polymer binder mixture. Specifically, the content of the third polymer binder may be 51 parts by weight to 69 parts by weight, 52 parts by weight to 68 parts by weight, 53 parts by weight to 67 parts by weight, 54 parts by weight to 66 parts by weight, 55 parts by weight to 65 parts by weight, 56 parts by weight to 64 parts by weight, 57 parts by weight to 63 parts by weight, 58 parts by weight to 62 parts by weight, or 59 parts by weight to 61 parts by weight based on 100 parts by weight of the polymer binder mixture. By controlling the content of the third polymer binder within the above range, it is possible to prevent the binder from sinking under the inorganic particles, thereby preventing a decrease in adhesive strength between the electrode and the separator.
[0100] According to an embodiment of the present invention, the content of the first polymer binder in a portion 131 adjacent to the polymer substrate in the thickness of the coating layer 130 may be greater than the content of the first polymer binder in another portion 133 not adjacent to the polymer substrate. Specifically, the portion 131 of the coating layer, which is a portion of the coating layer close to the polymer substrate, may contain a greater content of the first polymer binder than the other portion 131 of the coating layer, which is a portion of the coating layer far from the polymer substrate. As described above, the content of the first polymer binder is adjusted depending on the position of the coating layer, thereby improving the adhesive strength between the electrode and the polymer substrate and the coating layer. Specifically, the first polymer binder is excessively contained in the portion adjacent to the polymer substrate, which prevents the polymer binder from sinking under the inorganic particles and reducing the adhesive strength between the electrode and the separator.
[0101] In this specification, the thickness of a coating layer may refer to the width between one side of the coating layer on which the polymer substrate is provided and another side of the coating layer on which the polymer substrate is not provided, in a direction in which the coating layer is laminated on the polymer substrate.
[0102] According to one embodiment of the present invention, the content of the third polymer binder in the other portion 133 of the thickness of the coating layer 130 that is not adjacent to the polymer substrate may be greater than the content of the third polymer binder in the portion 131 adjacent to the polymer substrate. Specifically, the other portion 133 of the coating layer, which is a portion of the coating layer far from the polymer substrate, may contain a greater content of the third polymer binder than the portion 131 of the coating layer, which is a portion of the coating layer close to the polymer substrate. As described above, the content of the third polymer binder is adjusted according to the position of the coating layer, thereby improving the adhesive strength between the electrode and the polymer substrate and the coating layer. As described above, the content of the third polymer binder is adjusted according to the position of the coating layer, thereby improving the adhesive strength between the electrode and the polymer substrate and the coating layer. Specifically, since the third polymer binder is contained in an excess amount on the surface of the coating layer, the shape of the third polymer binder is maintained during the drying process of the applied coating layer, and thus the adhesive strength between the polymer substrate and the coating layer is prevented from decreasing, and the adhesive strength of the polymer binder itself is prevented from decreasing.
[0103] According to one embodiment of the present invention, the second polymer binder may be included in a uniform content in the coating layer 130. Specifically, the second polymer binder may be included in the same content in each of the coating layer portion 131 and the coating layer other portion 133 in the coating layer 130. As described above, by making the content of the second polymer binder the same regardless of the position, the cohesive force between the polymer binder and the inorganic particles in the coating layer can be improved.
[0104] According to one embodiment of the present invention, each of the first polymer binder, the second polymer binder, and the third polymer binder may be a mixture of one selected from the group consisting of an acrylic polymer resin, a vinylidene fluoride polymer resin, and a combination thereof, and / or a polymer of the mixture. According to one embodiment of the present invention, each of the first polymer binder, the second polymer binder, and the third polymer binder may be a mixture of one selected from the group consisting of an acrylic polymer resin, a vinylidene fluoride polymer resin, and a combination thereof, and / or a polymer of the mixture, in one particle. According to one embodiment of the present invention, the glass transition temperature of each of the first polymer binder, the second polymer binder, and the third polymer binder may be adjusted by changing the type and / or content of the component contained in each of the first polymer binder, the second polymer binder, and the third polymer binder. By selecting the first polymer binder, the second polymer binder, and the third polymer binder from the above, the adhesive strength between the polymer base material and the coating layer can be improved, the contact area between the other polymer binder and the inorganic particles can be increased to improve the cohesive strength, and a decrease in the dry adhesive strength can be prevented, and a decrease in the adhesive strength between the electrode and the separator due to the polymer binder sinking under the inorganic particles can be prevented.
[0105] According to one embodiment of the present invention, the acrylic polymer resin may be a polymer containing a carboxylate ester as a repeating unit, specifically, a (meth)acrylic ester. More specifically, the (meth)acrylic ester may be methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, n-amyl (meth)acrylate, i-amyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, (meth)acrylic ester, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, n-amyl (meth)acrylate, i-amyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl ... The (meth)acrylic ester may be one selected from the group consisting of decyl (meth)acrylate, hydroxymethyl (meth)acrylate, hydroxyethyl (meth)acrylate, ethylene glycol (meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, allyl (meth)acrylate, ethylene di(meth)acrylate, and combinations thereof. Preferably, the (meth)acrylic ester is one or more selected from methyl (meth)acrylate, ethyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. By selecting the acrylic polymer resin from the above, the mechanical properties of the coating layer can be improved, and the cohesive force with the polymer substrate can be improved.
[0106] According to one embodiment of the present invention, the acrylic polymer resin may be a copolymer containing styrene and acrylate in a weight ratio of 5:5 to 7:3. According to one embodiment of the present invention, the acrylate copolymerized with styrene may be butyl acrylate. In this case, if the content of the styrene is higher than the above range or the content of the acrylate is lower than the above range, the glass transition temperature (Tg) becomes high, which is undesirable since it may be difficult to form a dry state adhesive strength under the lamination process (50 to 80°C) conditions. If the content of the styrene is lower than the above range or the content of the acrylate is higher than the above range, the glass transition temperature (Tg) becomes low, which may cause the layer structure to collapse at room temperature, which is undesirable since it may be difficult to form a dry state adhesive strength.
[0107] According to one embodiment of the present invention, the vinylidene fluoride-based polymer resin may be an electrolyte-insoluble homopolymer of vinylidene fluoride, a copolymer of vinylidene fluoride and another polymerizable monomer, or a mixture of two or more of them.
[0108] According to one embodiment of the present invention, the vinylidene fluoride and other polymerizable monomers may include, but are not limited to, at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene, trifluoroethylene, chlorofluoroethylene, 1,2-difluoroethylene, perfluoro(methyl vinyl) ether, perfluoro(ethyl vinyl) ether, perfluoro(propyl vinyl) ether, perfluoro(1,3 dioxole), perfluoro(2,2-dimethyl-1,3-dioxole), trichloroethylene, and vinyl fluoride. In particular, the vinylidene fluoride-based polymer resin may be a copolymer of vinylidene fluoride and hexafluoropropylene. The content of vinylidene fluoride and other polymerizable monomers may be, but is not limited to, 1% by weight to 20% by weight of the copolymer.
[0109] In this specification, the content of the comonomer in the vinylidene fluoride-based polymer resin can be measured by 1H-NMR using Varian 500MHz. For details of the measurement method, refer to Journal of Materials Chemistry, 2012, 22, 341 or AMT-3412-0k. The NMR spectrum can be confirmed using suitable equipment such as Bruker Avance III HD 700Mhz NMR or Varian 500MHz NMR.
[0110] According to one embodiment of the present invention, the weight ratio of the acrylic polymer resin to the vinylidene fluoride polymer resin may be 9:1 to 1:9. If the content of the acrylic polymer resin is more than the range or the content of the vinylidene fluoride polymer resin is less than the range, wet state adhesive strength is not formed, which is not preferable, and if the content of the acrylic polymer resin is less than the range or the content of the vinylidene fluoride polymer resin is more than the range, dry state adhesive strength may be difficult to form, which is not preferable.
[0111] According to one embodiment of the present invention, the vinylidene fluoride-based polymer resin may be a copolymer crosslinked with a vinylidene fluoride-based polymer resin containing 10% by weight or less of hexafluoropropylene (HFP) and an acrylate in a weight ratio of 1:9 to 9:1. In this case, if the content of the vinylidene fluoride-based polymer resin is greater than the above range or the content of the acrylate is less than the above range, it is difficult to form a wet state adhesive strength, which is not preferable, and if the content of the vinylidene fluoride-based polymer resin is less than the above range or the content of the acrylate is greater than the above range, it is difficult to prepare a composition for forming a coating layer, which is not preferable.
[0112] According to one embodiment of the present invention, the acrylic polymer resin may be 4 wt% to 95 wt% and the vinylidene fluoride polymer resin may be 4 wt% to 95 wt% based on the total content of the first polymer binder, the second polymer binder, and the third polymer binder. If the content is outside this range, the resistance of the separator may increase and side effects such as difficulty in forming adhesive strength may occur.
[0113] One embodiment of the present invention provides a method for manufacturing the separator 100 for an electrochemical device, the method including: coating at least one surface of the polymer substrate 110 with a composition for forming a coating layer, the composition including inorganic particles and a polymer binder mixture including three or more polymer binders having different glass transition temperatures (S30); and drying the coated composition for forming a coating layer to form the coating layer (S50).
[0114] In a method for manufacturing a separator 100 for an electrochemical device according to an embodiment of the present invention, the cohesive force between the inorganic particles and the polymer binder can be improved by adjusting the temperature during the drying process, and the adhesive force between the polymer substrate 110 and the coating layer 130 and the adhesive force between an electrode (not shown) and the coating layer 130 can be improved by adjusting the contents of the first polymer binder and the third polymer binder according to the location of the coating layer 130.
[0115] 2 is a flow diagram of a method for manufacturing a separator 100 for an electrochemical device according to an embodiment of the present invention. The method for manufacturing a separator 100 for an electrochemical device according to an embodiment of the present invention will be described in detail with reference to FIG. 2. Furthermore, in this specification, the same parts as those described in the separator for the electrochemical device will be omitted.
[0116] According to one embodiment of the present invention, the method includes step S30 of coating a composition for forming a coating layer, which includes a polymer binder mixture including three or more polymer binders having different glass transition temperatures and inorganic particles, on at least one surface of a polymer substrate 110. As described above, by including step S30 of coating at least one surface of the polymer substrate 110 with the composition for forming a coating layer, which includes the polymer binder mixture including three or more polymer binders having different glass transition temperatures and the inorganic particles, a coating layer can be easily formed on the polymer substrate, thereby reducing the manufacturing time of the separator and allowing the separator to be mass-produced.
[0117] According to one embodiment of the present invention, the method for coating the composition for forming a coating layer on at least one surface of the polymer substrate may be a bar coater, a wire bar coater, a roll coater, a spray coater, a spin coater, an inkjet coater, a screen coater, a reverse coater, a gravure coater, a knife coater, a slot die coater, a hot melt coater, a comma coater, a direct metering coater, or the like, and the coating method may be applied without any limitation in the process of producing a separator.
[0118] According to one embodiment of the present invention, the method includes step S50 of drying the coated composition for forming a coating layer to form the coating layer 130. As described above, by including step S50 of drying the coated composition for forming a coating layer to form the coating layer 130, a coating layer can be easily formed on the polymer substrate, and the second polymer binder included in the composition for forming a coating layer can be prevented from sinking from the lower portion of the inorganic particles, i.e., the surface of the coating layer, toward the inside, thereby reducing the adhesive strength of the separator and reducing the cohesive strength between the polymer binder and the inorganic particles.
[0119] According to one embodiment of the present invention, the drying temperature may be 30° C. or more and 70° C. or less. Specifically, the drying temperature may be 31° C. or more and 69° C. or less, 32° C. or more and 68° C. or less, 33° C. or more and 67° C. or less, 34° C. or more and 66° C. or less, 35° C. or more and 65° C. or less, 36° C. or more and 64° C. or less, 37° C. or more and 63° C. or less, 38° C. or more and 62° C. or less, 39° C. or more and 61° C. or less, 40° C. or more and 60° C. or less, 41° C. or more and 59° C. or less, 42° C. or more and 58° C. or less, 43° C. or more and 57° C. or less, 44° C. or more and 56° C. or less, 45° C. or more and 55° C. or less, 46° C. or more and 54° C. or less, 47° C. or more and 53° C. or less, 48° C. or more and 52° C. or less, or 49° C. or more and 51° C. By adjusting the drying temperature within the above range, the cohesive strength of the coating layer itself can be improved, and the decrease in dry adhesive strength caused by the bond between the electrode and the separator being broken at high temperature can be prevented, and the decrease in adhesive strength caused by the polymer binder sinking below the inorganic particles can be prevented.
[0120] According to one embodiment of the present invention, the difference between the drying temperature and the glass transition temperature of the second polymer binder may be within 10° C. Specifically, the difference between the drying temperature and the glass transition temperature of the second polymer binder may be within 9° C., 8° C., 7° C., 6° C., 5° C., 4° C., 3° C., 2° C., or 1° C. By controlling the difference between the drying temperature and the glass transition temperature of the second polymer binder within the above range, the cohesive force of the coating layer itself is improved, and the bond between the electrode and the separator is prevented from being broken at high temperature, causing a decrease in dry adhesive force, and the polymer binder is prevented from sinking under the inorganic particles, causing a decrease in adhesive force.
[0121] According to one embodiment of the present invention, the method may further include a step S10 of preparing a composition for forming a coating layer including a polymer binder mixture containing three or more polymer binders having different glass transition temperatures and inorganic particles before the coating step S30. As described above, by further including a step S10 of preparing a composition for forming a coating layer including the polymer binder mixture containing three or more polymer binders having different glass transition temperatures and the inorganic particles before the coating step S30, the composition for forming a coating layer can be easily handled, the viscosity of the composition for forming a coating layer can be adjusted to adjust the thickness of the coating layer, and the rate at which the solvent of the composition for forming a coating layer is evaporated can be adjusted to adjust the formation rate of the coating layer.
[0122] According to one embodiment of the present invention, the method may further include a step of subjecting at least one surface of the polymer substrate to a corona discharge treatment. The step of subjecting at least one surface of the polymer substrate to a corona discharge treatment may be performed without limitation before the step S30 of coating at least one surface of the polymer substrate with a composition for forming a coating layer. Specifically, the polymer substrate in the step S30 of coating at least one surface of the polymer substrate with the composition for forming a coating layer may be one that has been subjected to the corona discharge treatment. As described above, by including a step of subjecting at least one surface of the polymer substrate to a corona discharge treatment, the adhesive strength between the surface of the polymer substrate and the surface of the coating layer at high temperatures is prevented from decreasing, and the adhesive strength between the surface of the polymer substrate and the surface of the coating layer is prevented from decreasing due to an electrolyte.
[0123] According to one embodiment of the present invention, the corona discharge treatment may be performed in air at a voltage of 0.1 kV to 10 kV. Specifically, the corona discharge treatment may be performed in air at a voltage of 0.2 kV to 9 kV, 0.3 kV to 8 kV, 0.4 kV to 7 kV, 0.5 kV to 6 kV, 0.6 kV to 5 kV, 0.7 kV to 4 kV, 0.8 kV to 3 kV, 0.9 kV to 2 kV, or 1.0 kV to 2 kV. Preferably, the corona discharge treatment may be performed in air at a voltage of 1.8 kV. By adjusting the applied voltage of the corona discharge treatment within the above range, an appropriate number of functional groups can be formed on the surface of the polymer substrate, thereby preventing damage to the surface of the polymer substrate.
[0124] One embodiment of the present invention provides an electrochemical device including a positive electrode, a negative electrode, and a separator 100 interposed between the positive electrode and the negative electrode, the separator 100 being a separator for the electrochemical device.
[0125] In an electrochemical device according to an embodiment of the present invention, peeling of a coating layer due to impact during the process of cutting and handling the separator 100 and during the process of assembling a battery can be prevented.
[0126] According to one embodiment of the present invention, the positive electrode comprises a positive electrode current collector and a positive electrode active material layer on at least one surface of the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a conductive material, and a binder resin. The positive electrode active material is a lithium manganese composite oxide (LiMn 2 O 4 , LiMnO 2 etc.), lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ) and compounds substituted with one or more transition metals; 1+x Mn 2-x O 4 (wherein x is 0 to 0.33), LiMnO 3 , LiMn 2 O 3, LiMnO 2 and other lithium manganese oxides; lithium copper oxide (Li 2 CuO 2 ); LiV 3 O 8 , LiV 3 O 4 , V 2 O 5 , Cu 2 V 2 O 7 and other vanadium oxides; nickel-site lithium nickel oxide represented by the chemical formula LiNi 1-x M x O 2 (where M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x = 0.01 to 0.3); lithium manganese composite oxide represented by the chemical formula LiMn 1-x M x O 2 (where M = Co, Ni, Fe, Cr, Zn or Ta, and x = 0.01 to 0.1) or Li 2 Mn 3 MO 8 (where M = Fe, Co, Ni, Cu or Zn); lithium manganese composite oxide in which a part of Li in the chemical formula is substituted with an alkaline earth metal ion; LiMn 2 O 4 ; disulfide compounds; Fe 2 (MoO 4 ) 3 It can contain one or a mixture of two or more of them.
[0127] According to one embodiment of the present invention, the negative electrode includes a negative electrode current collector and a negative electrode active material layer containing a negative electrode active material, a conductive material, and a binder resin on at least one surface of the negative electrode current collector. As the negative electrode active material, the negative electrode includes carbon such as lithium metal oxide, graphitizable carbon, and graphite-based carbon; LixFe 2 O 3 (0 ≦ x ≦ 1), Li x WO 2 (0 ≦ x ≦ 1), silicon-based materials such as Si, SiO x (0 < x < 2), SiC, and Si alloys; Sn x Me 1-x Me' y Oz (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8), etc. metal composite oxides; lithium metal; lithium alloy; tin-based alloy; SnO, SnO 2 , PbO, PbO 2 , Pb 2 O 3 , Pb 3 O 4 , Sb 2 O 3 , Sb 2 O 4 , Sb 2 O 5 , GeO, GeO 2 , Bi 2 O 3 , Bi 2 O 4 , and Bi 2 O 5 and metal oxides such as Bi 5 O
[0128] According to one embodiment of the present invention, the positive electrode current collector and / or the negative electrode current collector are not particularly limited as long as they do not induce a chemical change in the electrochemical element and have high conductivity. Specifically, stainless steel, copper, aluminum, nickel, titanium, fired carbon, or those surface-treated with carbon, nickel, titanium, silver, etc. on the surface of aluminum or stainless steel may be used.
[0129] According to one embodiment of the present invention, the conductive material may be any one selected from the group consisting of graphite, carbon black, carbon fiber or metal fiber, metal powder, conductive whisker, conductive metal oxide, carbon nanotube, activated carbon, and polyphenylene derivative, or a mixture of two or more of these conductive materials. The carbon nanotube has a graphite sheet in the form of a cylinder with a nanosize diameter and sp 2The graphite sheet has a bond structure and exhibits conductive or semiconductive properties depending on the angle and structure at which the graphite sheet is wound. Carbon nanotubes can be classified into single-walled carbon nanotubes (SWCNT), double-walled carbon nanotubes (DWCNT) and multi-walled carbon nanotubes (MWCNT) according to the number of bonds forming the wall, and these carbon nanotubes can be appropriately selected depending on the use of the dispersion. More specifically, the carbon nanotube may be one or a mixture of two or more conductive materials selected from the group consisting of natural graphite, artificial graphite, super-p, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate and titanium oxide.
[0130] According to an embodiment of the present invention, the binder resin may be any binder resin commonly used in electrodes in the art. Non-limiting examples of such binder resins include polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-cotrichloroethylene, polymethylmethacrylate, polyethylhexylacrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, ethylene-vinylacetate copolymer, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, and cellulose acetate propionate. Examples of suitable cellulose acetate copolymers include, but are not limited to, cyanoethyl acetatepropionate, cyanoethylpullulan, cyanoethylpolyvinylalcohol, cyanoethylcellulose, cyanoethylsucrose, pullulan, and carboxyl methyl cellulose.
[0131] According to one embodiment of the present invention, an electrode assembly includes a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode. The electrode assembly is placed in a suitable case and an electrolyte is injected into the case to manufacture an electrochemical device.
[0132] According to one embodiment of the present invention, the electrolyte is + B - A salt having the structure: + Li + , Na + , K + or a combination thereof, such as B - PF 6 - , B.F. 4 - , Cl - , Br - , I - , ClO 4 - , AsF 6 - , C.H. 3 CO 2 - , C.F. 3 SO 3 - , N(CF 3 SO 2 ) 2 - , C(CF 2 SO 2 ) 3 - or a salt containing an anion such as the above or a combination thereof may be dissolved or dissociated in an organic solvent such as propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma butyrolactone (γ-butyrolactone), or a mixture thereof, but is not limited thereto.
[0133] According to an embodiment of the present invention, there is provided a battery module including a battery including the electrode assembly as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source. Specific examples of the device include, but are not limited to, a power tool powered by a battery-type motor, electric vehicles including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), etc., electric two-wheeled vehicles including electric bicycles (E-bikes) and electric scooters (E-scooters), electric golf carts, and power storage systems. EXAMPLES
[0134] Hereinafter, the present invention will be described in detail with reference to examples. However, the examples according to the present invention can be modified in various other forms, and the scope of the present invention is not to be construed as being limited to the following examples. The examples in the present specification are provided to more completely explain the present invention to those having average knowledge in the art.
[0135] <Examples 1 and 2 and Reference Examples 1 to 4>
[0136] Production of composition for forming coating layer
[0137] Inorganic particles such as Al were added to distilled water at room temperature in a content ratio of 4 times the total content of the first polymer binder, the second polymer binder, and the third polymer binder. 2 O 3and polyacrylic acid as a dispersant were added, and then bead milling was performed (0.7 μm zirconia beads were added in the same weight as the inorganic particles, and milled for 2 hours using a paint shaker) to prepare an inorganic dispersion. A first polymer binder, a second polymer binder, and a third polymer binder having glass transition temperatures (Tg) as shown in Table 1 below were added to the inorganic dispersion in the weight ratios as shown in Table 2 below.
[0138] The first polymer binder is a copolymer of methyl methacrylate and 2-ethylhexyl acrylate, and was prepared to have a glass transition temperature as shown in Table 1 below by adjusting the weight ratio of methyl methacrylate and 2-ethylhexyl acrylate.
[0139] Each of the second polymer binder and the third polymer binder is a copolymer of styrene and butyl acrylate, and was prepared to have a glass transition temperature as shown in Table 1 below by adjusting the weight ratio of styrene and butyl acrylate.
[0140] In order to improve wettability with the polymer substrate, a siloxane-based surfactant was added as a surfactant, and the mixture was stirred at 10 rpm for 10 minutes to prepare a slurry, which is a composition for forming a coating layer in which the first polymer binder, the second polymer binder, the third polymer binder, and inorganic particles are dispersed.
[0141] Preparation of polymer substrate
[0142] A 9 μm-thick polyethylene film (PE, weight-average molecular weight 900,000, porosity 40% by volume) was used as a porous polymer substrate having a plurality of pores.
[0143] Separation membrane manufacturing
[0144] The slurry, which is the composition for forming a coating layer, was coated on both sides of the prepared polyethylene film, which is the polymer substrate, using a doctor blade, and then dried using a hot air blower to form coating layers with a thickness of 2.5 μm each, thereby producing a separator with a total thickness of about 14 μm.
[0145] <Comparative Example 1>
[0146] A separator was prepared in the same manner as in Example 1, except that the second polymer binder was not included in the composition for forming a coating layer of Example 1.
[0147] [Table 1]
[0148] [Table 2]
[0149] <Experimental Example 1: Measurement of Peel Strength>
[0150] Each of the separation membranes prepared in Examples 1-2, Comparative Example 1, and Reference Examples 1-4 was cut into 70 mm (length) x 15 mm (width) to prepare a specimen. The prepared specimen was attached and fixed to a slide glass using double-sided tape. Next, the end of the adhesive surface of the specimen (10 mm or less from the end of the adhesive surface) was peeled off, and a 25 mm x 100 mm PET film was attached to the length direction using a single-sided adhesive tape. Then, the slide glass was attached to the lower holder of the UTM equipment (LLOYD instrument LF Plus), and the separation membrane and the attached PET film were attached to the upper holder of the UTM equipment, and a force was applied in the 180° direction at a measurement speed of 300 mm / min to measure the force required to peel the separation membrane from the slide glass.
[0151] <Experimental Example 2: Measurement of adhesion between electrode and separator>
[0152] To measure the adhesive strength between the electrode and the separator, a negative electrode was prepared as follows.
[0153] First, for the negative electrode, artificial graphite, carbon black, carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were mixed with water in a weight ratio of 96:1:2:2 to prepare a negative electrode slurry. The negative electrode slurry was charged to 3.5 mAh / cm 2 The resulting mixture was coated on a copper foil in a volumetric capacity to form a thin electrode plate, which was then dried at 135° C. for 3 hours or more and pressed to prepare a negative electrode.
[0154] The prepared negative electrode was cut to a size of 2.5cm x 6cm. The separator prepared in the examples and comparative examples was cut to a size of 2.5cm x 6cm. The prepared separator and negative electrode were stacked on top of each other, sandwiched between 100μm PET films, and bonded using a flat press. The flat press conditions were heating and pressing at 80°C and a pressure of 6.5MPa for 1 second. The bonded separator and negative electrode were attached to a slide glass using double-sided tape. The end of the separator adhesive surface (10mm or less from the end of the adhesive surface) was peeled off, and the separator was attached to a 25mm x 100mm PET film and single-sided adhesive tape so that the length direction was connected. Then, the slide glass was attached to the lower holder of the UTM equipment (LLOYD instrument LF Plus), and the separator and the attached PET film were attached to the upper holder of the UTM equipment. A force was applied at 180° at a measurement speed of 300 mm / min to measure the force required to peel the negative electrode and the separator.
[0155] <Experimental Example 3: Measurement of the cohesion force of the coating layer>
[0156] Each of the separators prepared in Examples 1-2, Comparative Example 1, and Reference Examples 1-4 was cut into a specimen of 70 mm (length) x 15 mm (width). Using a SAICAS EN-EX device (DAILPLA WINTES), a blade was pressed into the specimen at an angle of 60° from the surface of the specimen, and the vertical and horizontal forces generated during the pressing process were measured, and the cutting force was calculated as the sum of the vectors of the two forces.
[0157] [Table 3]
[0158] Referring to Table 3, it was confirmed that in Comparative Example 1, in which the glass transition temperature of the first polymer binder was less than -40°C and no second polymer binder was included, the cohesive force between the inorganic particles and the third binder was low, and the peel strength was significantly reduced.
[0159] In comparison, it was confirmed that Examples 1 and 2, in which the first polymer binder had a glass transition temperature of -40°C to -20°C, the second polymer binder had a glass transition temperature of 0°C to 20°C, and the third polymer binder had a glass transition temperature of 30°C to 60°C, had improved cohesive strength and peel strength, and maintained the adhesive strength between the electrode and the separator. Additionally, it was confirmed that Reference Example 1, in which the glass transition temperature of the first polymer binder is less than -40°C, had weak retention of the first polymer binder between the polymer base material and the inorganic particles, resulting in reduced peel strength.
[0160] In addition, in Reference Example 2, in which the glass transition temperature of the second polymer binder is less than 0° C., it was confirmed that the adhesive strength and cohesive strength between the inorganic particles and the polymer binder were reduced.
[0161] Furthermore, in Reference Example 3, in which the glass transition temperature of the second polymer binder is higher than 20° C., sufficient cohesive strength is not secured during the drying process of a typical separator. When the temperature is increased to secure sufficient cohesive strength, the shape of the third polymer binder is distorted, decreasing the dry adhesive strength and thus the cohesive strength.
[0162] In addition, in Reference Example 4, in which the glass transition temperature of the first polymer binder is higher than -20°C, the particulate form of the polymer binder does not collapse during the drying process, but the adhesive strength between the polymer substrate and the coating layer decreases, resulting in a decrease in peel strength.
[0163] It has been confirmed that the separator for an electrochemical device, the manufacturing method thereof, and the electrochemical device including the same according to an embodiment of the present invention maintain the adhesive strength between the electrode and the separator and improve the cohesive strength and peel strength by controlling the glass transition temperature of the polymer binder contained in the coating layer.
[0164] In this specification, preferred embodiments of the present invention are disclosed and specific terms are used, but these are used in a general sense to simply explain the technical contents of the present invention and to aid in the understanding of the invention, and are not intended to limit the scope of the present invention. Furthermore, in the above description, the present invention has been described using limited embodiments, but the present invention is not limited thereto, and it is natural that various modifications and variations are possible within the technical spirit of the present invention and the scope of the claims described below, by those having ordinary skill in the art to which the present invention pertains.
[0165] [Explanation of symbols]
[0166] 100: Separation membrane for electrochemical devices 110: Polymer base material 130: Coating layer 131: A part of the coating layer 133: Other parts of the coating layer S10: Preparation of a composition for forming a coating layer S30: Coating stage S50: Drying stage
Claims
1. A separator for an electrochemical element, comprising: a polymeric substrate comprising a plurality of pores; a coating layer provided on at least one surface of the polymeric substrate, the coating layer including a plurality of pores and including a mixture of inorganic particles and a polymeric binder; having The polymer binder mixture comprises three or more polymer binders having different glass transition temperatures.
2. the polymeric binder mixture includes a first polymeric binder, a second polymeric binder, and a third polymeric binder; 2. The separator for an electrochemical device according to claim 1, wherein the first polymer binder, the second polymer binder, and the third polymer binder satisfy the following formula 1: [Formula 1] The glass transition temperature of the first polymer binder is smaller than the glass transition temperature of the second polymer binder and smaller than the glass transition temperature of the third polymer binder.
3. 3. The separator for an electrochemical device according to claim 2, wherein the first polymer binder has a glass transition temperature of -40°C or more and -20°C or less.
4. The separator for an electrochemical device according to claim 2 , wherein the second polymer binder has a glass transition temperature of 0° C. or more and 20° C. or less.
5. The separator for an electrochemical device according to claim 2 , wherein the third polymer binder has a glass transition temperature of 30° C. or more and 60° C. or less.
6. The glass transition temperature of the first polymer binder is −40° C. or more and −20° C. or less; The second polymer binder has a glass transition temperature of 0° C. or more and 20° C. or less; The separator for an electrochemical device according to claim 2 , wherein the third polymer binder has a glass transition temperature of 30° C. or more and 60° C. or less.
7. The content of the first polymer binder is 5 parts by weight or more and 15 parts by weight or less with respect to 100 parts by weight of the polymer binder mixture, The content of the second polymer binder is 20 parts by weight or more and 40 parts by weight or less with respect to 100 parts by weight of the polymer binder mixture, The separator for an electrochemical device according to claim 2 , wherein the content of the third polymer binder is 50 parts by weight or more and 70 parts by weight or less with respect to 100 parts by weight of the polymer binder mixture.
8. 3. The separator for electrochemical devices according to claim 2, wherein a content of the first polymer binder in a portion of the coating layer adjacent to the polymer substrate is greater than a content of the first polymer binder in another portion of the coating layer not adjacent to the polymer substrate.
9. 3. The separator for electrochemical devices according to claim 2, wherein a content of the third polymer binder in a portion of the coating layer not adjacent to the polymer substrate is greater than a content of the third polymer binder in a portion of the coating layer adjacent to the polymer substrate.
10. The separator for an electrochemical device according to claim 2 , wherein the second polymer binder is contained in the coating layer at a uniform content.
11. A method for producing a separator for electrochemical elements according to any one of claims 1 to 10, comprising the steps of: Coating at least one surface of the polymer substrate with a composition for forming a coating layer, the composition including the inorganic particles and the polymer binder mixture including three or more polymer binders having different glass transition temperatures; drying the coated composition for forming a coating layer to form the coating layer; The method for producing a separator for an electrochemical element comprises the steps of:
12. The method of claim 11, wherein the drying step is performed at a temperature of 30° C. to 70° C.
13. An electrochemical element comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, the separator being the separator for electrochemical elements according to any one of claims 1 to 10.
Citation Information
Patent Citations
Battery separator, lithium ion battery, and manufacturing method thereof
JP2019525442A
Separator containing binders with different glass transition temperatures and manufacturing method thereof
JP2020522097A
Separator for lithium secondary battery having improved electrode adhesion and resistance characteristics, and lithium secondary battery including the separator
JP2022544609A
Separator for electrochemical device and method for manufacturing same
JP2023518499A
Apparatus, method and computer-readable storage medium for providing platform of application service of bicycle based on calculating reduced carbon emission
KR102360491B1